Epidemiological Study of Tropical Diseases in Coastal Communities in the Context of Global Climate Change, in Tondonggeu Village, Nambo District, Kendari City - Ramadhan Tosepu; Muhammad Arifin; Pitrah Asfian; Melia Pradita Rohadi; Wa Ode Intan Aprilia; Dian Sari Aristianty; Michelin Alfa Saruran; Dhira Fijri Yasmin; Intan Marchella; Susi Indasari (Journal of Epidemiology and Health Science, 2025)
Background: Climate change has become a widely debated global issue due to its profound impact on multiple sectors of life, particularly public health. The potential risks posed by climate change to human health are increasingly recognized as a global challenge that threatens livelihoods and well-being. Climate change refers to alterations in climate patterns that occur directly or indirectly due to human activities, leading to changes in the global atmospheric composition. It also includes shifts in natural climate variability observed over comparable periods of time. Empirical data indicate that the vulnerabilities and risks associated with global climate change not only influence economic, social, and political spheres but also contribute to the emergence and exacerbation of various public health issues Objective: This study aims to examine the impact of global climate change on the incidence of tropical diseases specifically malaria, dengue fever, chikungunya, filariasis, and leptospirosis within coastal communities in Nambo District, particularly in Tondenggeu Village. Methods: This research employed a quantitative analytical approach with an observational design, using the cross-sectional method to assess the relationship between climate change and the prevalence of tropical diseases. Data were collected through structured questionnaires distributed to respondents residing in the study area. Results: Statistical analysis shows that there is no significant relationship between climate change variables and the incidence of tropical diseases with a P-value of 0.574 (P > 0.05). Conclusion: The results of this study indicate that there is no statistically significant relationship between climate change and the incidence of tropical diseases in the study population. Several limitations may have influenced the findings. Notably, inaccuracies in data collection may have occurred due to respondents’ reluctance to provide honest or accurate responses, which could compromise the validity of the results. These limitations should be taken into account in the interpretation of the study's findings and addressed in future research to improve data quality and reliability. Keywords: Chikungunya Fever, Cross-Sectional Studies, Leptospirosis, Filariasis, Climate Change, Public Health